RETRACTED: Mitigation of salinity stress in barley genotypes with variable salt tolerance by application of zinc oxide nanoparticles - Ali, Basharat; Saleem, Muhammad Hamzah; Ali, Shafaqat; Shahid, Munazzam; Sagir, Muhammad; Tahir, Muhammad Bilal; Qureshi, Kamal Ahmad; Jaremko, Mariusz; Selim, Samy; Hussain, Afzal; Rizwan, Muhammad; Ishaq, Wajid; et al. (Frontiers in Plant Science, 2022)
Salinity has become a major environmental concern of agricultural lands, impairing crop production. The current study aimed to examine the role of zinc oxide nanoparticles (ZnO NPs) in reducing the oxidative stress induced by salinity and the overall improvement in phytochemical properties in barley. A total of nine different barley genotypes were first subjected to salt (NaCl) stress in hydroponic conditions to determine the tolerance among the genotypes. The genotype Annora was found as most sensitive, and the most tolerant genotype was Awaran 02 under salinity stress. In another study, the most sensitive (Annora) and tolerant (Awaran 02) barley genotypes were grown in pots under salinity stress (100 mM). At the same time, half of the pots were provided with the soil application of ZnO NPs (100 mg kg–1), and the other half pots were foliar sprayed with ZnO NPs (100 mg L–1). Salinity stress reduced barley growth in both genotypes compared to control plants. However, greater reduction in barley growth was found in Annora (sensitive genotype) than in Awaran 02 (tolerant genotype). The exogenous application of ZnO NPs ameliorated salt stress and improved barley biomass, photosynthesis, and antioxidant enzyme activities by reducing oxidative damage caused by salt stress. However, this positive effect by ZnO NPs was observed more in Awaran 02 than in Annora genotype. Furthermore, the foliar application of ZnO NPs was more effective than the soil application of ZnO NPs. Findings of the present study revealed that exogenous application of ZnO NPs could be a promising approach to alleviate salt stress in barley genotypes with different levels of salinity tolerance.